Retour à Douchanbe - Mirzoeva, Gulya (France, 2000)
In 1992, shortly before the outbreak of civil war in Tajikistan, the filmmaker went to France. Seven years later she returned - conscious of the distance. The film is a series of portraits about her return to the native land of Tajikistan, where she presents the memories of the place, current realities and the changes that have taken place since she left.
Soros Documentary Fund
Soros Documentary Fund
Keywords: Documentary films